2022
DOI: 10.1038/s42255-022-00620-x
|View full text |Cite
|
Sign up to set email alerts
|

BMP4 and Gremlin 1 regulate hepatic cell senescence during clinical progression of NAFLD/NASH

Abstract: The role of hepatic cell senescence in human non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) is not well understood. To examine this, we performed liver biopsies and extensive characterization of 58 individuals with or without NAFLD/NASH. Here, we show that hepatic cell senescence is strongly related to NAFLD/NASH severity, and machine learning analysis identified senescence markers, the BMP4 inhibitor Gremlin 1 in liver and visceral fat, and the amount of visceral adipose ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 67 publications
2
17
1
Order By: Relevance
“…Additionally, it improved dyslipidemia and reduced liver enzymes and triglycerides synthesis. This is in accordance with prior studies reporting improved hepatic steatosis by AICAR [ 38 , 52 ]. AMPK reportedly mediates AICAR’s beneficial metabolic actions; active Thr172 phospho-AMPK exhibits an anti-lipogenic effect by suppressing hepatic expression and activities of lipogenic enzymes and activates β oxidation [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, it improved dyslipidemia and reduced liver enzymes and triglycerides synthesis. This is in accordance with prior studies reporting improved hepatic steatosis by AICAR [ 38 , 52 ]. AMPK reportedly mediates AICAR’s beneficial metabolic actions; active Thr172 phospho-AMPK exhibits an anti-lipogenic effect by suppressing hepatic expression and activities of lipogenic enzymes and activates β oxidation [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Hepatic steatosis is a common finding in obesity, diabetes mellitus (DM) and metabolic syndrome (MS) with numerous complex biochemical, metabolic, and clinical manifestations. Several anti-diabetic drugs such as metformin and other AMPK activators have been widely used to treat NAFLD, yet their exact mechanism(s) of action in NAFLD remains largely obscure [ 38 ]. The old drug, AICAR, has drawn attention for its potential AMPK-independent actions at the cellular level [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Gremlin-1 has been recognised as a potential therapeutic target in treating patients with MASH, and MASH fibrosis in particular. Baboota et al recently suggested that anti-Gremlin-1 based therapies may be able to halt or even reverse MASH progression through inhibition of hepatocellular senescence (20). In the present study, we aimed to develop and evaluate anti-Gremlin-1 neutralising antibodies as therapeutic assets for the treatment of MASH fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, expression generally is low (16) and restricted to activated hepatic stellate cells, which are the main fibrogenic cell population in the liver along with fibroblasts (17,18). Hepatic Gremlin-1 has been linked to hepatocellular insulin resistance (19) and recent literature described a role in driving hepatocellular senescence, which in turn is linked to hepatic fibrogenesis and carcinogenesis (20). Previous evidence suggests that Gremlin-1 plays an active role in liver fibrosis by inhibiting the anti-fibrotic action of BMPs 4 and 7 on activated hepatic stellate cells (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Prominent members of this class include rapamycin, metformin, resveratrol, glucosamine, curcumin analogs, and simvastatin (Cherif et al., 2019; Fuentes‐Fayos et al., 2023; Hooten et al., 2016; W. Li et al., 2019; N. Wang et al., 2016; M. Xu et al., 2015). Key markers of cellular senescence, such as β‐Gal, p16, p21, and p53, have been found to be elevated in liver cells in nonalcoholic fatty liver disease (NAFLD), and further in nonalcoholic steatohepatitis (NASH), and related to the amount of liver fat; thus suggesting that liver senescence may be a primary factor in the development of NAFLD/NASH (Baboota et al., 2022). Other approaches include rejuvenating the immune system and modulating SASP through signaling pathways such as histone lysine demethylase 4 (KDM4).…”
Section: “Old” Hallmarks Of Aging—longevity Perspectivementioning
confidence: 99%